Decomposition of mixtures of cover crop residues increases microbial functional diversity - Drost, Sytske M.; Rutgers, Michiel; Wouterse, Marja; de Boer, Wietse; Bodelier, Paul L.E. (Geoderma, 2020)
•Microbial biomass is increased more gradually during decomposition of cover crop mixtures compared to monocultures.•Microbial functional diversity is higher in cover crop mixtures.•Nutrient content of cover crops is the main driver for nutrient release. To improve sustainability in agricultural systems, winter cover crops are increasingly replacing fallow to stimulate soil functions that reduce nutrient losses and greenhouse gas production, reduce pests for the next cash crops, increase soil organic matter pools and reduce erosion. Several of these functions are highly dependent on soil microbes decomposing cover crop residues. Since cover crop species differ in their traits it is hypothesized that plant species residue mixtures with complementary characteristics perform better by stimulating soil microbial functional diversity. To test this, residues of cover crop monocultures and mixtures were mixed with agricultural soil in a microcosm experiment, and fungal and bacterial biomass, microbial metabolic potential, greenhouse gas emissions and soil nutrients were measured during 50 days. Fungal biomass increased for all treatments compared to the control (no additions). However, there were no significant differences between cover crop mixtures and monocultures. Biolog ECO plates were used as a proxy for the metabolic potential of the microbial community. The number of substrates used was significantly higher in soil amended with residues of cover crop mixtures indicating an increased number of substrate niches for microbes. C:N ratio of cover crop residues was shown to be an important variable in explaining dynamics of CO2 and N2O emissions. Mixtures of cover crops showed reduced N2O and CO2 emissions compared to monocultures at the start of the experiment, but did not reduce greenhouse gas emissions over the whole incubation period. Adding nitrogen to the cover crop treatment with the highest C:N ratio (oat) did increase N2O emissions, but not CO2 emissions suggesting that decomposition rate of oat residues is not limited by nitrogen availability. Overall, mixtures of cover crops stimulated microbial functional diversity in soil incubations. Although this may have positive implications for soil quality and functioning in agricultural fields, further studies are needed to verify if these results hold under field conditions.